FELDSPAR SATURATION STATE IN NATURAL WATERS - Stefánsson A.; Arnórsson S. (My University, 2000)
The saturation state of feldspar minerals in natural waters ranging from 0°C to over 300°C was studied. Waters above 200°C have closely approached equilibrium with microcline and low-albite. This is consistent with the occurrence of these minerals as hydrothermal minerals in active geothermal systems with temperature in excess of some 200°C. The Na+/K+ activity ratio of geothermal waters with temperature as low as 50°C closely approaches that predicted from thermodynamic data for the reaction low-albite + K+ = microcline + Na+, suggesting that Na and K ion activities in these geothermal waters are controlled by simultaneous equilibrium with these two feldspars. Geothermal waters are undersaturated with primary disordered plagioclases and alkali-feldspars of compositions typically found in volcanic rocks. Accordingly these feldspars tend to dissolve in such waters simultaneously with precipitation of ordered alkali-feldspars. Surface- and non-thermal groundwaters are usually undersaturated with respect to igneous and metamorphic feldspars regardless of composition and Al-Si ordering and tend, therefore, to dissolve under weathering conditions.